What Are the Different Strategies for EMU Countries? - Patrick Artus (Vierteljahrshefte zur Wirtschaftsforschung, 2006)
The answer to competition from emerging countries with low wage costs must be very different according to the affected sector. We need to draw a distinction between manufacturing industry and services that can be relocated and other sectors: consumer services, retail, construction, most business services and financial services. For the former, no obstacle to restructuring or the modernisation of companies can be efficient, even though this implies further relocations and job losses. For the latter, there is a crucial need to analyse and assess the various experiments that seek to stimulate job creation in said sectors, as this is indispensable if industry is to continue losing jobs. We complete the analysis of the strategy of the various countries in manufacturing by a research of the determinants of exports performance.
Keywords: 330; Internationaler Wettbewerb; Dienstleistungssektor; Industrie; Arbeitsmarktpolitik; Export; Outsourcing; Eurozone; Deutschland; Italien; Frankreich